1998
DOI: 10.1302/0301-620x.80b3.0800531
|View full text |Cite
|
Sign up to set email alerts
|

Cellular profile and cytokine production at prosthetic interfaces

Abstract: T he tissues surrounding 65 cemented and 36 cementless total joint replacements undergoing revision were characterised for cell types by immunohistochemistry and for cytokine expression by in situ hybridisation.We identified three distinct groups of revised implants: loose implants with ballooning radiological osteolysis, loose implants without osteolysis, and well-fixed implants. In the cemented series, osteolysis was associated with increased numbers of macrophages (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 47 publications
2
25
0
1
Order By: Relevance
“…For example, the concentrations of M-CSF, TNF-␣, IL-6, and IL-1 in synovial fluid and/or in serum of rheumatoid arthritis patients are extremely high (24, 46 -49). In aseptic loosening, IL-1, IL-6, and TNF-␣ are present in the tissue surrounding failed implants (25,26,50). It was also reported that TNF-␣ promoted bone resorption by activating mature osteoclasts or by stimulating proliferation and differentiation of osteoclasts indirectly via a primary effect on osteoblasts (20 -23).…”
Section: Table I Effects Of M-csf Pretreatment On the Tnf-␣-induced Tmentioning
confidence: 99%
“…For example, the concentrations of M-CSF, TNF-␣, IL-6, and IL-1 in synovial fluid and/or in serum of rheumatoid arthritis patients are extremely high (24, 46 -49). In aseptic loosening, IL-1, IL-6, and TNF-␣ are present in the tissue surrounding failed implants (25,26,50). It was also reported that TNF-␣ promoted bone resorption by activating mature osteoclasts or by stimulating proliferation and differentiation of osteoclasts indirectly via a primary effect on osteoblasts (20 -23).…”
Section: Table I Effects Of M-csf Pretreatment On the Tnf-␣-induced Tmentioning
confidence: 99%
“…Wear particles within the critical size range were found to be more influential, in the stimulus of cytokines, than those outside the critical size [9,11,12].…”
Section: Introductionmentioning
confidence: 95%
“…However, there are several factors that affect the durability of the total hip joint prosthesis, one of which is bearing surface wear (and related phenomena). It is postulated that wear of the UHMWPE cup causes premature failure of hip joint prostheses [8,9]. Wear debris from component materials was found to initiate the macrophage activation, which can lead to a cytochemical response, resulting in bone resorption around the prosthesis and subsequent aseptic loosening and early failure of the prosthesis [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these facts, we conclude that the methodology is a well-validated immunologic technique. The results concerning the role of immune responses to the biomaterials used in THR have been contradictory (Chadha et al 1995, Haddad et al 1996, Goodman et al 1998, Weyand et al 1998. The reported percentages of lymphocytes have varied in interface tissue from aseptic loosening of THR (Lalor et al 1991, Jiranek et al 1993, Boynton et al 1995 found a higher number of total T-cells and IL-2R positive T-cells in the patients with loosened THR than in those without loosening.…”
Section: Discussionmentioning
confidence: 99%